(untitled) (The International Journal for Scientific Research, 2025)
This study aimed to explore the concepts of waste and profligacy, their interrelationship, and their implications. The study followed a descriptive approach, and its main objectives included understanding the concepts of waste and profligacy, examining their interconnection, discussing the ruling on profligacy in Islam and its evidence, identifying the causes leading to it, and exploring its various forms and negative consequences. Additionally, the study examined the role of Islamic education in addressing profligacy through religious and educational means, such as promoting Islamic values in society, guiding individuals toward moderation in spending, and fostering awareness about the dangers of waste. The theoretical framework of the research was divided into three sections: the first section discussed the concepts of waste and profligacy, the second examined the Islamic ruling on profligacy, and the third reviewed the forms and negative effects of profligacy. The research concluded that Islamic education plays a crucial role in combating profligacy by enhancing religious and social awareness and guiding individuals toward moderate behaviors, contributing to the development of a balanced and sustainable society.